Palm oil mills odour emission survey based on different POME treatment system - Yap, Andrew Kian Chung; Nastaein Qamaruz Zaman; Fatah Yah Abd. Manaf; Rohaya Mohamed Halim; Rusnani Abd. Majid (Penerbit Universiti Kebangsaan Malaysia, 2021)
Odorous gaseous such as ammonia and hydrogen sulphide produced by anaerobic bacteria are emitted when palm oil mill effluent (POME) is treated via anaerobic digestion. The Department of Environment (DOE) under the jurisdiction of the Air Division has proposed an odour emission limit of 12,000OUm-3 at source sample for Malaysian palm oil mills recently. The objective of this paper is to investigate the odour concentration at effluent treatment area within palm oil mills which practise different types of common POME treatment systems such as Open Ponds Treatment, Covered Lagoon and Digester Tank. The odour source grabbed samples from the respective treatment plants were assessed according to MS 1963:2007 Air Quality – determination of odour concentration by dynamic olfactometry. In addition in-situ odour concentration surrounding the respective project sites have been measured based on enhanced procedures adapted from VDI3940 Grid Method. The survey results showed that odour emitted from Open Ponds Treatment was having highest concentration while Digester Tank was having the lowest concentration due to quarantine factor. None of the observations comply the DOE proposal. Thus, alternative approaches need to be counter proposed in the legislation drafting so that the millers compliance could be ensured while avoid the public sensory annoyance complaints.